Kilka uwag na temat metodologii badań prowadzonych wśród osób w wieku senioralnym - Jaroszewska, Anna (Neofilolog, 2010)
The purpose of the article is to draw attention to the specific nature of pedagogical research carried out in research groups represented by people in late adulthood. On the basis of the characteristics of the last stage of a person’s development, the author attempts to indicate such research methods and techniques and such an approach to them as will enable the optimization of broadly understood research upon the process of foreign language learning by elderly people.